The governmentality of teaching and learning: acquiescence or resistance? - Dalgliesh, Bregham (Critical Studies in Teaching and Learning, 2023)
This article critiques the ethics of teaching and learning (T&L) practices in the university. It argues they consummate contemporary regimes of government through the backdoor of the classroom.  To this end, the university is first depicted as an organisation opened up by the imperatives of advanced liberalism.  The article then examines Henry Giroux’s critical pedagogy, which links the cultivation of critical citizens to a democratic polity.  However, Giroux’s proposal for student emancipation through juxtaposing knowledge with power is rejected in favour of a Foucauldian framework  of  governmentality. It understands the teaching and learning regimes (TLRs) of active learning as a solution to the imperatives of the conduct of conduct incited by advanced  liberal  government,  which  traditional  T&L practices  of  passive  learning  are  unable  to  satisfy.  The innocuousness of  these  changes  in student  conduct  is  subsequently  interpreted  in  terms  of  its  ethical  import.  Following Michel Foucault’s demarcation of  ethics  from  morality,  four  elements  of  ethics  are  discerned  and mapped onto TLRs: the ethical substance, or what to act on (mind); the ethical work, or how to  act  upon  (individualisation);  the  mode  of  subjectification,  or who must  act  (autonomous learners); and the ethical conduct, or why we must act (self-entrepreneurial subjects). Finally, the  article  suggests  the  academic’s  purgatory  between  their  former  identity  as  a  teacher  and their current role as an instructor can be resolved in the classroom itself through an agonistic ethical relation to the student, which is simultaneously a form of resistance of TLRs.